PEMASARAN PRODUK DAN KUALITAS PRODUK TERHADAP MINAT KONSUMEN PADA MATAHARI DEPARTMENT STORE - Nur Aini Anisa; Nur Farida; Kurniawati Kurniawati; Evi Aulia Rachma (Bajang Institute, 2023)
This study aims to determine the effect of product marketing and product quality on consumer interest. This research method is quantitative using multiple linear regression data analysis techniques with the help of SPSS. The sampling technique in this study used purposive sampling with a sample size of 100 respondents. The results showed that product marketing and product quality had an effect on consumer interest in Matahari department store either partially or simultaneously